TRAINING IN BREEDING FOR USED AGARWOOD COMMODITY NORTH ACEH DISTRICT CONFLICT AREA - Wardah, Eva; Setia Budi; Lukman (RADJA PUBLIKA, 2023)
Agarwood is a type of wood produced by several species of trees from the Aquilaria genus, especially Aquilaria malaccensis. Agarwood has high value in the perfume and traditional medicine industries because of its unique aromatic compounds. Agarwood can be formed due to interactions between microbes (certain inoculum) and host plants and chemical mechanisms that ultimately form a product, namely sapwood. Local inoculum is effective in producing gaharu, because it is endemic to certain areas. Some of the partners' obstacles that are strongly felt include (1) the low ability of farmer group members in terms of breeding agarwood plants both naturally (generatively) including propagation treatments using mature seeds and saplings (plucks) as well as plant cutting patterns. (2) There is no knowledge and skills of members of the two partner groups in carrying out the breeding and maintenance of gaharu seedlings. This service uses training and seeding methods for seed patterns and saplings (plucks) and plant cuttings. This method is appropriate to use where the participation of partner farmers in improving skills and the mentoring process is carried out directly by practicing. The pattern of implementing community service activities for partner farmers applies the principle of